Biomechanical evaluation of oblique lateral interbody fusion with various fixation methods for degenerative lumbar scoliosis: a finite element analysis considering different bone densities - Guo, Wei; Wang, Zemin; Song, Meina; Yang, Wei; Zhang, Honglai; Yang, Wanzhong; Wang, Shiyong; Ma, Rong; Ge, Zhaohui (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundFew studies have been conducted on the biomechanical stability of oblique lumbar interbody fusion (OLIF) in conjunction with different fixation methods in patients with degenerative lumbar scoliosis (DLS) at varying bone densities. This study uses finite element analysis to assess the biomechanical stability of OLIF with various fixation techniques for treating DLS under differing bone densities.MethodsA three-dimensional finite element model of the lumbar spine (L1-S1) was created using CT scans from a Lenke-Silva IV DLS patient. The control group consisted of a posterior lumbar interbody fusion (PLIF) model. The experimental groups included OLIF Stand Alone (OLIF-SA), OLIF combined with unilateral pedicle screw fixation (UPSF), and OLIF combined with bilateral pedicle screw fixation (BPSF) models. Three bone density conditions—normal bone mass (NBM), osteopenia, and osteoporosis—were used to evaluate these models. The range of motion (ROM) of the surgical segment, the stress distribution of the Cage, endplate, and internal fixation, as well as the peak Von Mises stress, were evaluated by applying a vertical downward load of 400N and a torque of 7.5N·m in different directions.ResultsUnder different bone densities, compared to the PLIF model, the ROM of the surgical segment in the OLIF-SA model was significantly increased, whereas the ROM in the OLIF-UPSF and OLIF-BPSF models was similar to or lower than that of the PLIF. Under NBM and osteopenia, both OLIF-UPSF and OLIF-BPSF effectively reduced the peak Von Mises stress on the endplate and maintained surgical segment stability. However, under osteoporosis, the peak Von Mises stress on the endplate in the OLIF-UPSF model approached or exceeded the maximum yield stress of the endplate (60 MPa) in certain motion states, while OLIF-BPSF demonstrated superior biomechanical stability. Additionally, variations in bone density significantly affected the stress distribution of internal fixation devices, with more uniform stress observed in the OLIF-BPSF model under osteoporosis conditions.ConclusionOLIF-BPSF may provide the best biomechanical stability for patients with DLS, especially osteoporosis patients. However, in patients with NBM and osteopenia, OLIF-UPSF remains an effective treatment option, which can ensure good biomechanical stability while obtaining significant minimally invasive advantages.